PREDICTION OF THE THERMODYNAMIC PROPERTIES AND RELATIVE STABILITY OF ANHYDRITE - Dubrovinskiy L.S.; Rubin S.G.; Iskhakova K.D.; Urusov R.S. (My University, 1990)
The dehydration of gypsum CaSO4·H2O and the crystal structure of the resulting compounds have often been investigated. But the published data on the temperature intervals in which the various phases can exist in the CaSO4·2H2O-CaSO4 system, the mechanisms of phase transitions, and the compositions and structures of the lower hydrates are contradictory. This paper reports an analysis of one of the phase relationships in this system, namely, the conversion of the polymorphic modifications γ-CaCO4 (space group P622) → anhydrite, i.e., rhombic β-CaSO4 (space group Cmom).